Topographical Organization of M-Current on Dorsal and Median Raphe Serotonergic Neurons - Bayasgalan, Tsogbadrakh; Csemer, Andrea; Kovacs, Adrienn; Pocsai, Krisztina; Pal, Balazs (Frontiers in Cellular Neuroscience, 2021)
Dorsal and median raphe nuclei (DR and MR, respectively) are members of the reticular activating system and play important role in regulation of sleep-wakefulness cycle, movement and affective states. M-current is a voltage-gated potassium current under the control of neuromodulatory mechanisms setting neuronal excitability. Our goal was to determine the proportion of DR and MR serotonergic neurons possessing M-current and whether they are organized topographically. Electrophysiological parameters of raphe serotonergic neurons influenced by this current were also investigated. We performed slice electrophysiology on genetically identified serotonergic neurons. Neurons with M-current are located rostrally in the DR and dorsally in the MR. M-current determines firing rate, afterhyperpolarization amplitude and adaptation index of these neurons, but does not affect input resistance, action potential width and high threshold oscillations. These findings indicate that M-current has a strong impact on firing properties of certain serotonergic neuronal subpopulations and it might serve as an effective contributor to cholinergic and local serotonergic neuromodulatory actions.